2018
DOI: 10.2147/cmar.s171661
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key candidate genes and small molecule drugs in cervical cancer by bioinformatics strategy

Abstract: PurposeCervical cancer (CC) is one of the most common malignant tumors among women. The present study aimed at integrating two expression profile datasets to identify critical genes and potential drugs in CC.Materials and methodsExpression profiles, GSE7803 and GSE9750, were integrated using bioinformatics methods, including differentially expressed genes analysis, Kyoto Encyclopedia of Genes and Genomes pathway analysis, and protein–protein interaction (PPI) network construction. Subsequently, survival analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Our results indicated that RRM2 is upregulated and significantly associated with poor prognosis in cervical cancer, and these results are in line with previous studies [18,19,36,40]. With 192 samples (29 normal, 30 low-grade dysplasia, 30 high-grade dysplasia and 103 invasive cancer tissue specimens) and SiHa cervical cancer cells, Su et al reported the expression of RRM2 in cancer tissues was increased when compared to high-grade dysplasia, low-grade dysplasia or normal cervical tissues [40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results indicated that RRM2 is upregulated and significantly associated with poor prognosis in cervical cancer, and these results are in line with previous studies [18,19,36,40]. With 192 samples (29 normal, 30 low-grade dysplasia, 30 high-grade dysplasia and 103 invasive cancer tissue specimens) and SiHa cervical cancer cells, Su et al reported the expression of RRM2 in cancer tissues was increased when compared to high-grade dysplasia, low-grade dysplasia or normal cervical tissues [40].…”
Section: Discussionsupporting
confidence: 93%
“…They also found that downregulated RRM2 promoted apoptosis and cell cycle arrest, as well as inhibiting tumor formation. In addition, bioinformatics analyses also indicated that OS was significantly better in the low-expression RRM2 group [18,36].…”
Section: Discussionmentioning
confidence: 95%
“…5D; Table 3) included: (1) YTA7/ATAD2/ATAD2B , which localizes to chromatin and regulates histone gene expression. ATAD2 overexpression portends poor prognosis in gastric, colorectal, cervical, hepatocellular carcinoma, lung, and breast cancer, and thus overexpression sensitivity could represent the potential to target a driver gene [119-125]; (2) PIF1 / PIF1 , a DNA helicase, which is involved in telomere regulation and is required during oncogenic stress [113]; (3) RPS1B/RPS3A , which is a small subunit ribosomal protein that is overexpressed in hepatitis B associated hepatocellular carcinoma and non-small cell lung cancer [114,115]; (4) LEO1/LEO1 , which associates with the RNA polymerase II and acts as an oncogene in acute myelogenous leukemia [156]; (5) ELO3/ELOVL1/ELOVL2/ ELOVL4/ELOVL6 , which constitutes a family of fatty acid elongases that function in sphingolipid biosynthesis, among which ELOVL1 is overexpressed in breast and colorectal cancer tissue [107,108], ELOVL2 is upregulated in hepatocellular carcinoma [109], and ELOVL6 is overexpressed and associated with poor prognosis in liver and breast cancer [110,111] ; (6) MDL2/ABCB10 , which is a mitochondrial inner membrane ATP-binding cassette protein and is upregulated in breast cancer [112]; (7) CPR3/PPIA , which is a mitochondrial cyclophilin that is upregulated in lung cancer, esophageal, and pancreatic cancer [104-106]; and (8) SAC3/MCM3AP/SAC3D1 , which is a nuclear pore-associated protein functioning in transcription and mRNA export, with MCM3AP being upregulated in glioma cells [116], while SAC3D1 is upregulated in cervical cancer and hepatocellular carcinoma [117,118]. Yeast gene deletion suppression together with overexpression sensitivity of human homologs in cancer reveals potential therapeutic vulnerabilities that can be further explored in both systems.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, one new approach for the use of MCM2 as a biomarker is the detection of its gene in samples. Tang et alusing bioinformatics analysis, concluded that the MCM2 gene plays an essential role in cervical cancer, and it might represent an important marker for diagnosis [144].…”
Section: Top2a and Mcm2mentioning
confidence: 99%